Changing spatial patterns and increasing rurality of HIV prevalence in the Democratic Republic of the Congo between 2007 and 2013. (May 2016) - Carrel, Margaret; Janko, Mark; Mwandagalirwa, Melchior Kashamuka; Morgan, Camille; Fwamba, Franck; Muwonga, Jérémie; Tshefu, Antoinette K.; Meshnick, Steven; Emch, Michael
Abstract: The Democratic Republic of the Congo (DRC) has one of the lowest HIV prevalence in sub-Saharan Africa, estimated at 1.1% [0.9–1.3] of adults aged 15–49 in 2013 (UNAIDS). Within the 2 million km 2 country, however, there exists spatial variation in HIV prevalence, with the highest HIV prevalence observed in the large cities of Kinshasa and Lubumbashi. Globally, HIV is an increasingly rural disease, diffusing outwards from urban centers of high HIV prevalence to places where HIV was previously absent or present at very low levels. Utilizing data collected during Demographic and Health Surveillance (DHS) in 2007 and 2013 in the DRC, we sought to update the map of HIV prevalence in the DRC as well as to explore whether HIV in the DRC is an increasingly rural disease or remains confined to urban areas. Bayesian kriging and regression indicate that HIV prevalence in rural areas of the DRC is higher in 2013 than in 2007 and that increased distance to an urban area is no longer protective against HIV as it was in 2007. These findings suggest that HIV education, testing and prevention efforts need to diffuse from urban to rural areas just as HIV is doing. Highlights: While overall prevalence of HIV remains low in the DRC, the spatial patterns of HIV have changed between 2007 and 2013. In 2007, rural residence far from urban areas was protective against HIV. In 2013, rural residence is no longer protective against HIV. Women in the DRC, regardless of residential location, have higher HIV risk than men. HIV is diffusing from urban to rural areas in the DRC.